APLIKASI MODEL SISTEM DINAMIS UNTUK MENGANALISIS PENJUALAN SEMEN X DI KOTA X - Endar Ernanda; Misra Hartati (Spektrum Industri, 2019)
Cement is an important main ingredient to construct a building. The large demand for cement in Indonesia made cement companies competed each other to attract consumers. PT Semen X is one of the well-known cementproducers in X City. This company sells some variant of cement, one of them is cement X. Nevertheless, sales of cement X is stilll under the forecast set by the company. This study aims to understand the factors that influence cement sales and take a policy to increase sales of cement X in the X City area. Calculations are carried out using a dynamic system method. The simulation was designed for 12 months in 2019. Based on the results of the dynamic system design, it was found that the sales and income of PT. Semen X increases every month. Furthermore, two scenarios are designed to increase sales and revenue of PT. Semen X. According to the simulation results, the first scenario was chosen, namely the addition of online promotion variables affected the value of the promotion of cement products X. This will give a significant influence on the sales and incomeof PT. Sement X.